In-Vitro Anti-Plasmodial Activities of Ethanolic Extracts of Adansonia digitata, Morinda citrifolia, and Tamarindus indica Against Plasmodium falciparum - Hamza, Mariya Musa; Yahaya Abdullahi, Umar; Sani Abdulsalami, Mohammed; Godwin, Onwumere; Gabi, Baba; Alkali, Kaumi (Sahel Journal of Life Sciences FUDMA, 2024)
Malaria due to Plasmodium species is an existential problem and a major disease in many developing countries. The emergence of drug-resistant parasites and the limited availability of effective treatments present major challenges in combating this disease. Thus, searching for more potent antimalarial agents, especially from natural sources, has become urgent and imperative. This study investigates the anti-plasmodial properties of the ethanolic crude extracts of Adansonia digitata (stem bark), Morinda citrifolia (leaves), and Tamarindus indica (leaves) using standard methods. The crude plant extracts were obtained using the maceration technique using 70% ethanol. The in vitro anti-plasmodial activities of the crude extracts were assessed using the Plasmodium lactate dehydrogenase (pLDH) assay against asexual stages of clinical isolates of P. falciparum maintained at 5% haematocrit (human type O+ red blood cells) in complete RPMI-1640 medium. The crude ethanolic extracts of T. indica exhibited a significantly higher (p < 0.05) in vitro anti-plasmodial activity with an IC50 value of 5.86μg/mL, followed by A. digitata (IC50 = 30.22μg/mL,) and M. citrifolia (IC50 = 31.85μg/mL). The findings in this study indicated that the crude extracts tested showed potential for anti-plasmodial activities that could be harnessed for developing novel anti-plasmodial agents.